MAKEPUNG TRADITION: AESTHETICS OF ESSAY PHOTOGRAPHY THROUGH EDFAT AND SKIN MEDIA TRANSFER - I Dewa Putu Ari Kresna Artha Negara; I Wayan Karja; I Komang Arba Wirawan; Ni Wayan Ardini (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This study is to identify the makepung tradition in Jembrana Regency, Bali, through essay photography. Research methods: The process of creating this photographic work begins with designing a concept with ideas, themes, and objects to be created, namely the makepung tradition in essay photography. The EDFAT theory, namely entire, detail, frame, angle, and time is applied as the basis for the theory of creation. Cowhide is used as a print medium for the photo essay. The process starts from skin selection, drying, and editing to printing photos on the leather media. Findings: Makepung is the peak of the joy of the farmers in being grateful for their harvest. Photographic essays in the series photo genre are composed of pure photographic works, into photos with writings that aim to tell the tradition. The photo works convey messages through photo essays of the tradition. Implications: This creation can provide new experiences for creators and the community to make photo essays or series so that people know the series of makepung tradition events from beginning to end.